(untitled) (Fiep Bulletin - online, 2011)
The purpose of this article was to compare the body satisfaction of women with different body mass indices enrolled in gymnastics. We conducted a field survey with the sample of 45 women enrolled in an academy in the southern zone of São Paulo. The subjects were divided into 15 groups: Normal, Overweight and Obese second WHO, attended two or more times per week, more than six months and the length of stay longer than thirty minutes per session and by weight measurement and height and three questionnaires, identification and sample selection, range Silhouettes and Body Shape Questionnaire (BSQ). The results show that excess body fat interferes with the quality of life for many women suffer from this problem even those who are close to the body desirable for today’s society, because even being with body mass index within the normal range, ie those considered normal or normal weight or reduce your silhouette, and were gravely dissatisfied bodily second test BSQ. The main objective was to perform physical exercise by the Aesthetic Obese group and did not provide data on the objective of Lazer and might not think of it as something pleasurable. It is observed that these obese women more than others, should be worried about the health data for obesity lead the Quality of Life. Anyway, who suffers in body dissatisfaction are women who are overweight and obese, the preoccupation with health is broken by the quest for aesthetics, then rethink the role that physical education has within the Academies to improve the quality of life will to improve self-esteem, self-concept and body satisfaction, and thus avoiding the possibility of triggering other illnesses.